An uncommon source for oesophageal foreign body: Fidget spinner. (9th June 2018) - Saadeh, Charles; Ulualp, Seckin O
Fidget spinner is a new handheld toy with potential choking and ingestion hazard. Our objectives are to describe clinical presentation of a child with fidget spinner ingestion and draw attention to danger associated with fidget spinner. A 3-year-old boy presented with painful swallowing and feeling of something stuck in the throat. A chest radiograph revealed a radiopaque foreign body with a disc-like component. Rigid oesophagoscopy revealed a foreign object with disc battery and battery holder circuit board. Clinicians should consider the fidget spinner as one of many varieties of toys that has potential for button battery ingestion or aspiration.